Pembentukan Karakter Peserta Didik dalam Kegiatan Ekstrakurikuler Randai di MTs Ibadurrahman Lolo - Adinda Putri; Hengki Armez Hidayat (Departement of Mathematics Education, 2023)
activities at Mts Ibadurrahman Lolo. The type of research used is qualitative research with descriptive methods. The research instrument was the researcher himself who played a role in collecting data and information on research objects by conducting field observations, and was equipped with stationery and cellphones to document the research process. In this study, the types of data used are primary data and secondary data. Data collection techniques in this study were carried out using observation/direct observation, interviews, literature study and documentation. Then the procedure for analyzing the data in this study was carried out with the stages of data reduction, data collection, as well as verification and concluding. From the results of the study, it was found that Randai's extracurricular activities were a means for developing students' talents in the field of performing arts. Randai extracurricular activities at MTs Ibadurrahman Lolo are carried out in several stages, namely; 1) activity planning, 2) activity implementation, and 3) evaluation of Randai extracurricular activities. Character building in Randai extracurricular activities contains several aspects, namely; 1) the value of customs, 2) historical education, 3) cultural education, 4) discipline, 5) cooperation, 6) creative, 7) curiosity, 8) love of the motherland, and 9) moral values.